Perkembangan Musik Pop Indonesia - Irgi Rechansyah Gani; Kiki Zakiah Darmawan (UNISBA Press, 2023)
Abstract. The phenomenon of reciting old Indonesian popular music from the 60-90s era is increasingly circulating everywhere, social media timelines, cafes, and many other unique mediums are widely listened to by Gen Z who incidentally were not born or even experienced the era that music first appeared. However, one thing that is missing from the phenomenon of the glittering Indonesian pop music today is the ongoing debate about what pop music really is, what underlies it's success. This study examines audience reception as readers of the book